Kontribusi Kompensasi, Motivasi, Sarana Prasarana dan Lingkungan Kerja terhadap Kinerja Guru Non Sertifikasi pada Madrasah Tsanawiyah (MTs) Swasta di Kabupaten Tabanan - Wahyuni, Tri Ayu; Sunu, I Gusti Ketut Arya; Dantes , Kadek Rihendra (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to determine the magnitude of the significant simultaneous contribution between compensation, motivation, infrastructure and work environment on the performance of non-certified teachers at private Madrasah Tsanawiyah (MTs) in Tabanan Regency. The type of research used in this study is quantitative using a correlational study type of research. The population in this study were teachers at private Madrasah Tsanawiiyah in Tabanan Regency, both those with ASN status, Permanent Foundation Teachers or Non-Permanent (Honorary) Teachers. Sampling uses saturated sampling, namely 58 teachers. Methods of data collection by observation, questionnaires, interviews, and documentation. The collected data were analyzed by descriptive analysis, Simple Linear Regression Analysis, and Multiple Regression Linear Analysis, as well as t test and F Level Significance test. The results of the study show that there is a significant simultaneous contribution of compensation, motivation, infrastructure and work environment to the performance of non-certified teachers at private Madrasah Tsanawiyah (MTs) in Tabanan Regency. 66% of teacher performance is influenced by compensation, motivation, infrastructure and work environment, the rest is influenced by other factors not mentioned in this study